Mercury released from dental "silver" fillings provokes an increase in mercury- and antibiotic-resistant bacteria in oral and intestinal floras of primates. - Summers, A O (1993)
In a survey of 640 human subjects, a subgroup of 356 persons without recent exposure to antibiotics demonstrated that those with a high prevalence of Hg resistance in their intestinal floras were significantly more likely to also have resistance to two or more antibiotics. This observation led us to consider the possibility that mercury released from amalgam ("silver") dental restorations might be a selective agent for both mercury- and antibiotic-resistant bacteria in the oral and intestinal floras of primates. Resistances to mercury and to several antibiotics were examined in the oral and intestinal floras of six adult monkeys prior to the installation of amalgam fillings, during the time they were in place, and after replacement of the amalgam fillings with glass ionomer fillings (in four of the monkeys). The monkeys were fed an antibiotic-free diet, and fecal mercury concentrations were monitored. There was a statistically significant increase in the incidence of mercury-resistant bacteria during the 5 weeks following installation of the amalgam fillings and during the 5 weeks immediately following their replacement with glass ionomer fillings. These peaks in incidence of mercury-resistant bacteria correlated with peaks of Hg elimination (as high as 1 mM in the feces) immediately following amalgam placement and immediately after replacement of the amalgam fillings. Representative mercury-resistant isolates of three selected bacterial families (oral streptococci, members of the family Enterobacteriaceae, and enterococci) were also resistant to one or more antibiotics, including ampicillin, tetracycline, streptomycin, kanamycin, and chloramphenicol. While such mercury- and antibiotic-resistant isolates among the staphylococci, the enterococci, and members of the family Enterobacteriaceae have been described, this is the first report of mercury resistance in the oral streptococci. Many of the enterobacterial strains were able to transfer mercury and antibiotic resistances together to laboratory bacterial recipients, suggesting that the loci for these resistances are genetically linked. Our findings indicate that mercury released from amalgam fillings can cause an enrichment of mercury resistance plasmids in the normal bacterial floras of primates. Many of these plasmids also carry antibiotic resistance, implicating the exposure to mercury from dental amalgams in an increased incidence of multiple antibiotic resistance plasmids in the normal floras of nonmedicated subjects.